27‐3: High Performance Fringe Field Switching Mode Liquid Crystal Display with Photo‐alignment Technology for Vehicular Application. Issue 1 (30th May 2018) - Mizusaki, Masanobu; Tsuchiya, Hiroshi; Minoura, Kiyoshi; Ogawa, Katsuya; Taniike, Koshiro; Fujihara, Toshiaki
Abstract : We have developed a novel photo‐alignment FFS‐LCD (PA‐FFS‐LCD) with a wide nematic temperature range from ‐40°C to 95°C. Our developed PA‐FFS‐LCD shows fast gray‐to‐gray response time (< 20 ms at 25°C and < 300 ms at ‐30°C), wide viewing angle, and high contrast ratio over 1500. Image sticking was not recognized owing to a suitable configuration of pixel and common electrodes. The developed LCD can be used for vehicular application.